2012
DOI: 10.1002/lt.22475
|View full text |Cite
|
Sign up to set email alerts
|

A 7-gene signature of the recipient predicts the progression of fibrosis after liver transplantation for hepatitis C virus infection

Abstract: Fibrosis recurrence after liver transplantation (LT) for hepatitis C virus (HCV) is a universal event and strongly determines a patient's prognosis. The recipient risk factors for fibrosis recurrence are still poorly defined. Here we assess a genetic risk score as a predictor of fibrosis after LT. The cirrhosis risk score (CRS), which comprises allele variants in 7 genes (adaptorrelated protein complex 3 S2, aquaporin 2, antizyme inhibitor 1, degenerative spermatocyte homolog 1 lipid desaturase, syntaxin bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The rate of hepatic fibrosis progression is the main characteristic of the patient since the patients with the rapid progression of fibrosis to cirrhosis are the first candidates for antiviral therapy of chronic hepatitis C. Along with universally recognized risk factors that have an influence on the rate of hepatic fibrosis progression, significant role belongs to genetic markers. Comparison of genetic studies with clinical materials demonstrated the existence of a significant effect of the genetic polymorphism on this process in patients with chronic hepatitis C, however, the analysis of the complex impact of clinical data and genetic polymorphism was carried out in only a few works [2,13,17,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hepatic fibrosis progression is the main characteristic of the patient since the patients with the rapid progression of fibrosis to cirrhosis are the first candidates for antiviral therapy of chronic hepatitis C. Along with universally recognized risk factors that have an influence on the rate of hepatic fibrosis progression, significant role belongs to genetic markers. Comparison of genetic studies with clinical materials demonstrated the existence of a significant effect of the genetic polymorphism on this process in patients with chronic hepatitis C, however, the analysis of the complex impact of clinical data and genetic polymorphism was carried out in only a few works [2,13,17,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in murine models of liver fibrosis the expression of TLR4 on hepatic stellate cells appears to be functionally more relevant than its expression on KCs 4. In line with these data in mice, human genetic studies have also provided strong evidence for a link between TLR4 and the risk of developing severe hepatitis C virus-induced liver fibrosis before and after liver transplantation 7 8. While most of the latter studies have focused on liver fibrosis as the main outcome measure, the role of TLR signalling in other types of liver diseases—for example, alcoholic and non-alcoholic fatty liver, is less well defined 9 10…”
mentioning
confidence: 90%
“…Limited other studies have focused on other gene regions. Evidence from a single study links recipients with higher cirrhosis risk scores to progression post-LT (30). On the other hand, a separate locus strongly predictive of cirrhosis—PNPLA3—had no significant association with progression after HCV-related LT (31).…”
mentioning
confidence: 99%